PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI GERAK DAN LAGU - Mariana Panji Ramadan; Jimatul Arobbi (Institut Madani Nusantara, 2022)
Social development is one of the key aspects of development used in PAUD learning. This is shown through playing with peers, collaborative action with friends, and a sense of responsibility. The problem with this research is: “The movement of children's social emotional development by playing gymnastics and songs at RANurul Mu'minin Bojonggenteng Sukabumi?. The purpose of this study was to apply gymnastic games and songs to the social and emotional development of children by RA Nurul Mu'minin Bojonggenteng Sukabumi. the decision was to use a qualitative descriptive type and focus on teachers and students. The data acquisition tools used by the author in this study were observation, interviews, and documentation. Socio-emotional development of class B1 students RA Nurul Mu'minin Bojonggenteng, based on the data in the table above, based on the results of RANurul Mu'minin Bojonggenteng Sukabumi the percentage of up to 10 students 20% has not developed, 50% is starting to develop , 30% as expected, 0% very well developed. It can be said that it is the social and emotional development of the child through physical play and singing in RA. Nurul Mu'minin Bojonggenteng Sukabumi is growing very rapidly.